Study on 5G wireless network enhancement technology for time sensitive networks - Jincan XIN; Sen XU; Hua ZHANG; Shangkun XIONG; Hua XU (Dianxin kexue)
5G deterministic network is a new type of industrial communication technology vigorously promoted by the international industry.3GPP had introduced the time-sensitive communication technology to facilitate deterministic transmission.Compared with ultra-reliable and low-latency communication technology, time-sensitive communication technology further enhanced the 5G network in terms of delay jitter and time synchronization to realize the end-to-end time sensitive communication.Characteristics of time sensitive communication technology were analyzed.Based on the time-sensitive networking and 5G network converged architecture, the time-sensitive communication technology reduces the time synchronization error through the accurate time synchronization mechanism.Additionally, the scheduling enhancement mechanism was introduced to reduce the transmission delay.Furthermore, the Ethernet header compression mechanism was proposed to improve transmission efficiency.